Komunikačně-stylový a systémový pohyb v současné češtině - Čechová, Marie (Stylistyka, 2020)
The Czech language is socially stratified and regionally differentiated, although there are also processes of the opposite character going on in it, like unification and equalization. Language development includes in itself antinomies opposing each other, but which are mutually complementary and converting into each other. The paper presents an interpretation of the functioning of selected antinomies in the language and in speech, such as the relationship between the standard and non-standard forms, represented by the common Czech. As early as in the middle of the last century the tendency to blurring of boundaries between them occurred, while various linguists have had different opinions on that process. These opinions are reflected in inconsistencies present in normative books (dictionaries, grammars, orthographic norms, normative educational handbooks), and this raises the uncertainty of users in the choice of language means. The users are now perhaps more influenced by the media than by teaching. The level of media speech is reflected in the speech of ordinary users, the frequent phenomena being overused, they become fashion, they insinuate themselves into the speech regardless of their functionality or non-functionality. In general, the current situation of the Czech can be characterized as dynamic, with developmental features, both systemic and irregular. Linguistics should not only capture this situation and describe it, but influence it by linguistic awareness, as the followers of the Prague School claimed. However, some linguists refuse it, considering it wrongly as intervention and manipulation.